Identification of the agroclimatic suitability in the municipality of Fusagasuga (Cundinamarca) for pea crop (Pisum sativum L.), using participatory mapping - Martínez-Maldonado, Fabio Ernesto; Gómez-Latorre, Douglas Andrés; Araujo-Carrillo, Gustavo Adolfo; Rodríguez-Roa, Andrea Onelia; Estupiñan-Casallas, Jhon Mauricio; Deantonio-Florido, Leidy Yibeth; Bolaños-Benavides, Martha Marina (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2021)
Pea crop is highly vulnerable to the negative impacts of variability and climate change, due to its socioeconomic and environmental marginality, as well as the poor use of technical tools such as agroclimatic information. Therefore, in order to understand the local pea growers perception of agroclimatic risk, a participatory mapping experience implemented in the rural area of the municipality of Fusagasuga was performed. Edaphoclimatic constraints and opportunities of the Municipality for pea crop were identified. The exercise started with the dissemination of local climatic data and thematic cartography related to biophysical variables like elevation and slope. Local descriptions of soil characteristics were defined with the community to identify areas with the most and the least limiting soil conditions for pea crop. In addition, the areas with greater susceptibility to water deficit and water excess were identified. The paper emphasizes on the methodological and pedagogical process generated for the identification of agroclimatic risks. The results show how participatory learning empowers communities with information to improve their own knowledge of the territory. This approach contributes to the adaptative capacity to extreme weather events since it provides elements for community organization to face risk. The participatory approach allowed the identification of Aguadita, Bermejal, Tierranegra, La Palma, Bochica, Batan, Santa Lucía, El Guavio y El Carmen as low-risk areas for pea production due to their soil advantages and low occurrence of water deficit and water excess events.